A Comparison between the Morphologies and Structures of Dwarf Galaxies with and without Active Massive Black Holes - Seth J. Kimbrell; Amy E. Reines; Jenny E. Greene; Marla Geha (The Astrophysical Journal, 2023)
We study the morphologies and structures of 57 dwarf galaxies that are representative of the general population of dwarf galaxies and compare their demographics to a sample of dwarf galaxies hosting optically selected active galactic nuclei (AGNs). The two samples span the same galaxy stellar mass (10 ^9 ≲ M _⋆ / M _⊙ ≲ 10 ^9.5 ) and color range, and the observations are well-matched in physical resolution. The fractions of irregular galaxies (14%) and early types/ellipticals (∼18%) are nearly identical among the two samples. However, among galaxies with disks (the majority of each sample), the AGN hosts almost always have a detectable (pseudo)bulge, while a large fraction of the non-AGN hosts are pure disk galaxies with no detectable (pseudo)bulge. Central point sources of light consistent with nuclear star clusters are detected in many of the non-AGN hosts. In contrast, central point sources detected in the AGN hosts are, on average, more than 2 orders of magnitude more luminous, suggesting the point sources in these objects are dominated by AGN light. The preference for (pseudo)bulges in dwarf AGN hosts may inform searches for massive black holes in dwarf galaxies and attempts to constrain the black hole occupation fraction, which, in turn, has implications for our understanding of black hole seeding mechanisms.